Living related liver transplantation: medical and social aspects of a controversial therapy. Issue 2 (1st February 2002) - Broelsch, C E; Testa, G; Alexandrou, A; Malagó, M
Abstract : There are more than 15 000 patients waiting for a liver transplant in the USA, with an average waiting time of 468 days and a mortality rate as high as 15–20%. Until artificial organs or xenotransplantation becomes a reality, living donor liver transplantation remains the best option for patients with end stage liver disease.